THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP, COMPENSATION AND MOTIVATION ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE IN THE RIAU ISLANDS PROVINCIAL HEALTH OFFICE - Kristina Harahap; Chablullah Wibisono; Wayan Catra Yasa (RADJA PUBLIKA, 2024)
This study aims to examine the influence of transformational leadership, compensation and motivation on employee performance with job satisfaction as an intervening variable in the Riau Islands Provincial Health Service. The analysis used in this research is parametric and non-parametric statistics using SEM-PLS (Structural Equation Modeling). -Partial Least Square) Data analysis with parametric and non-parametric statistics regarding research variables, calibration tests / pilot tests, validity and reliability, Outer model and inner model analysis, as well as discussion of the results of hypothesis testing or Path Analysis. This research uses path analysis to test relationship patterns that reveal the influence of a variable or set of variables on other variables, both direct and indirect influences. The path coefficient calculation in this research was assisted by SmartPLS. The results of this research on the direct relationship found that there is a significant influence between Transformational Leadership, compensation, Motivation on job satisfaction, there is a significant influence between Transformational Leadership and motivation on employee performance at the Riau Islands Provincial Health Service and there is no significant influence between satisfaction work on employee performance, in the indirect relationship there is a significant influence between Transformational Leadership and Compensation on employee performance with job satisfaction as an intervening variable at the Riau Islands Provincial Health Service, and there is no significant influence between motivation on employee performance and job satisfaction as a variable intervening at the Riau Islands Provincial Health Service